SISTEM ANIMASI LED KUBUS 3 DIMENSI 4x4x4 BERBASIS VISUAL BASIC - , AYU SARASWATI; , Catur Atmaji, S.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the marketing, most businesses only utilize billboards to display around the road to promote their business. LED cube utilization can be used to increase the competitiveness to promote their products. Since LED cubes can form, text product or company logo. Using ATmega16 connected with visual basic as LED cube control interface, we can make a couple of animations that can be controlled directly by the user. The system is controlled by a visual basic interface to control the LED either flash individually. Is or to make microcontroller to be executed by the microcontroller the program by iterations animation, and the result is a series of Flash LED on the LED cube. With the many kinds of animated LED cube, it can be used to support the means of advertising, entertainment and arts. This system can also be controlled directly by the user via a visual basic interface that can be used as needed.